Identification of Tuna and Skipjack Fish Texture Using GLCM With Naive Bayes Classification - Muzakir Hi. Sultan; Ruslan Laisouw (Agrikan: Jurnal Agribisnis Perikanan, 2020)
Fish in Indonesian waters have various types, the famous ones are tuna and skipjack. The two types of fish look similar, because they come from the same family, namely scombridae. To find out and differentiate types of tuna and skipjack fish, it can be seen based on the texture image. The method that can be used in analyzing texture is the Gray Level Coocurent Matrix (GLCM) method. There are several methods of image classification, one of which is the Naive Bayes method. This study aims to identify types of tuna and skipjack based on texture analysis using the GLCM and Naive Bayes methods. Based on the results of testing data analysis on types of tuna and skipjack meat using GLCM with angles  and , the distance of each pixel is 1, indicating the value of Energy, Entropy Contrast, Homogeneity, Correlation, Sum Average, and Sum of Variance are highly varies. As well as the Naive Bayes classification results obtained a probability of 0.58 or 58% categorized as tuna meat, while the remaining probability of 0.42 or 42% is categorized as skipjack.